PEMBELAJARAN BERKERANGKA ELPSA UNTUK MENINGKATKAN HASIL BELAJAR STATISTIKA PADA SISWA KELAS VII MTS ASY-SYAFI’IYAH BENDUNG - Hartina, Hartina; Sanapiah, Sanapiah; Yuliyanti, Sri (Media Pendidikan Matematika, 2019)
Based on the research that has been done in VII grade student of MTs Asy-Syafi'iyahBendung found a problem that has an average mathematics value low. This iscaused  by learning  mathematics is still conventional and monotonous. So, there needs to be an effort to improve student learning outcomes. One of them is by applying the ELPSA framework learning. The purpose of this action research is to improve the learning outcomes at VII grade student of MTs Asy-Syafi'iyahBendungin academic year 2017/2018. The type of this research is Classroom Action Research (CAR). This research consisted 4 stages of CAR (Planning, Implementation, Observation and Reflection). The subject of this research are30 student at VII grade.The study was conducted within 6 weeks. The instruments in this research are daily tests, evaluation tests, and LKS. The results of research showed that student learning outcomes improved after applying ELPSA framework. Student?s completeness scor in cycle I is 30,76% increased to 86.7% in cycle II. Then it can be concluded that the implementation of ELPSA frame work on subject matter statistic can to improve student learning outcomes at VII grade student of MTs Asy-Syafi'iyah Bendung academic year 2017/2018.